Помогите, плиз, решить это. Нужны подробные решения!! Опишите всё, как решали.Заранее...

0 голосов
22 просмотров

Помогите, плиз, решить это. Нужны подробные решения!! Опишите всё, как решали.Заранее спасибо
\frac{x^2(4x^2+2)}{(x-1)^2} + \frac{x^2-4x^4}{x^2-2x+1} - \frac{3x(x-1)+3}{(1-x)^2} =
\frac{8y^3-8y^2-4y-3}{8y^2+4y+2} =


Алгебра (4.9k баллов) | 22 просмотров
Дан 1 ответ
0 голосов

1)(4x^4+2x²+x²-4x^4-3x²+3x-3)/(x-1)²=(3x-3)/(x-1)²=3(x-1)/(x-1)²=3/(x-1)
2)(8y³-8y²-4y-3)/2(4y²+2y+1)=(2y-3)/2
8y³-8y²-4y-3  |4y²+2y+1
8y³+4y²+2y        2y-3
------------------
     -12y²-6y-3
     -12y²-6y-3
     ----------------
             0